Apparent Carbon Monoxide Insertion via Double Isocyanide Incorporation during Palladium‐Catalyzed Construction of Indoloquinoline Ring in a Single Pot: Synthesis of New Cytotoxic Agents. Issue 21 (24th October 2016) - Nallapati, Suresh Babu; Prasad, Bagineni; Sreenivas, B. Yogi; Sunke, Rajnikanth; Poornachandra, Y.; Kumar, C. Ganesh; Sridhar, B.; Shivashankar, S.; Mukkanti, K.; Pal, Manojit
Abstract: The formation of an amide bond via incorporation of two isocyanide units during a palladium‐catalyzed construction of the indoloquinoline ring afforded N ‐substituted 6 H ‐indolo[2, 3‐ b ]quinoline‐11‐carboxamides as new cytotoxic agents. The solvent and base play a key role in the selective and unprecedented synthesis of this class of amides. Abstract :